Quality of Drinking Water in the Town of Manta in Benin Republic - Kelome Nelly Carine; Chouti Waris; Lawani Rébecca Annick Niréti; Olou Pélagie (European Scientific Journal, ESJ, 2018)
The current research was undertaken in the north of Benin Republic, to assess the pollution level of drinking water; with an emphasis on water sources (boreholes, wells, surface water, and fountain post) and water storage by households. To this end, five villages of the town of Manta were the target. The methodologywas based on chemical and bacteriological analyses of water samples collected in October 2015, from ten water sources and four households. The results of chemical analyzes, revealed that two out of five (5) boreholes sampled, had higher than normal nitrate concentrations. Two (2) wells out of three (3) had high ammonium concentrations. As far as the bacteriological aspect is concerned, water from the boreholes and wells are contaminated with fecal germs (Escherichia coli and fecal streptococcus). There is also a large presence of mesophilic aerobic germs and coliform flora in all samples. On the other hand, lithological data from drill holes, in the study area, indicate a preponderance of various schist and alterites that are depleted of fluorides and phosphate compounds. The geological cross-section shows that the aquifer in the town seems to be very homogeneous and does not indicate any tectonic structure that could explain contamination due to horizontal flow. This contamination reflects the lack of hygiene and sanitation near water storage points, the uncontrolled use of pesticides and fertilizers. The use of water protection equipment and hygiene awareness will considerably reduce pollution at the household level.